Effect of varying engine parameters and syngas composition on the combustion characteristics, performance and emission of syngas-diesel dual fuel engine - A review - Mahgoub, B.K.M. (Asian Research Publishing Network, 2015)
In this study, a literature survey of research papers on the effect of engine load, injection timing and syngas composition on the combustion characteristics performance and emission of dual fuel compression ignition (CI) engine using syngas was carried out. In general, operation of CI diesel engine with syngas leads to reduced engine power because syngas has lower heating value compared to diesel. However, dual fuel operation is considered as a hopeful way to control the emissions of nitrogen oxides on CI diesel engines and it affects positively on emissions of carbon dioxide, whereas it leads to a substantial increase in emissions of carbon monoxide and total hydrocarbons compared to the observed in the process of normal diesel. Advanced injection timing of diesel fuel and supercharging of the intake air-syngas mixture are techniques suggested to improve the engine performance. In addition varying of the syngas composition; especially combustible constituents (H2, CO, and CH4) combined with exclusion of CO2 from syngas composition are proposed as a way to improve engine performance and reduce emissions. Â© 2006-2015 Asian Research Publishing Network (ARPN).